2020
DOI: 10.1101/2020.01.29.924415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dynamics of the improvising brain: a study of musical creativity using jazz improvisation

Abstract: One of the defining elements of jazz is the ability to improvise. The neuroscience of jazz improvisation has shown promising results for understanding domain-specific and domaingeneral processes of creativity. However, until date no previous studies have examined how different modes of improvisation (musical creativity) evolve over time and which cognitive mechanisms are responsible for different stages of musical creation. Here, we used fMRI to measure for the first time the dynamic neural substrates of music… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 77 publications
(143 reference statements)
0
7
0
Order By: Relevance
“…We applied a novel method to capture patterns of functional connectivity from fMRI data at single TR resolution with reduced dimensionality, the Leading Eigenvector Dynamics Analysis (LEiDA) (Alves Da Mota et al, 2020;Cabral et al, 2017;Figueroa et al, 2019;Lord et al, 2019;E.A. Stark et al, 2020).…”
Section: Dynamic Functional Connectivity Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…We applied a novel method to capture patterns of functional connectivity from fMRI data at single TR resolution with reduced dimensionality, the Leading Eigenvector Dynamics Analysis (LEiDA) (Alves Da Mota et al, 2020;Cabral et al, 2017;Figueroa et al, 2019;Lord et al, 2019;E.A. Stark et al, 2020).…”
Section: Dynamic Functional Connectivity Analysismentioning
confidence: 99%
“…If instead the first eigenvector V 1 (t) has elements of different signs (i.e., positive and negative), the BOLD signals project into different directions with respect to the leading eigenvector, which naturally divides the brain into distinct modes (colored in red and blue in Figure 1B middle panels). Previous studies using LEiDA have shown that the subset of brain areas whose BOLD signals appear temporally phase-shifted from the main BOLD signal orientation reveal meaningful functional brain networks (Alves Da Mota et al, 2020;Cabral et al, 2017;Figueroa et al, 2019;Lord et al, 2019;E.A. Stark et al, 2020).…”
Section: Dynamic Functional Connectivity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…There are many answers to this question: historical (Hersch, 2008;Hughes and Brown, 1982), pedagogical (Kratus, 1995), sociocultural (Anderson, 2007), and neurobiological (Mota et al, 2020). Phenomenologically, we can describe improvisation in the jazz context as the exploration of a possibility space.…”
Section: Original Contributions -Originalbeiträgementioning
confidence: 99%